Jagatpur Ashram : Unoshotturpara, Raojan, Chittagong, Bangladesh - Khan, Muzaiana Naomi (BRAC University, 2013)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.